http://isrctn.org/> 2013
DOI: 10.1186/isrctn41221647
|View full text |Cite
|
Sign up to set email alerts
|

Chiropractic Manipulation in Adolescent Idiopathic Scoliosis: a pilot study

Abstract: Background: Adolescent idiopathic scoliosis (AIS) remains the most common deforming orthopedic condition in children. Increasingly, both adults and children are seeking complementary and alternative therapy, including chiropractic treatment, for a wide variety of health concerns. The scientific evidence supporting the use chiropractic intervention is inadequate. The purpose of this study was to conduct a pilot study and explore issues of safety, patient recruitment and compliance, treatment standardization, sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 15 publications
(20 reference statements)
0
27
0
1
Order By: Relevance
“…Among all of the studies reviewed here, only one had a randomized clinical trial design 20 ; another was a times series cohort. 14 The remaining studies were case series or case reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among all of the studies reviewed here, only one had a randomized clinical trial design 20 ; another was a times series cohort. 14 The remaining studies were case series or case reports.…”
Section: Discussionmentioning
confidence: 99%
“…One of the studies, by Rowe et al, was a randomized controlled clinical trial involving 6 patients. 20 This study was methodologically the strongest of any study we retrieved. The patients were randomized into different groups receiving different combinations of therapy.…”
Section: Manipulation Plus Bracingmentioning
confidence: 94%
“…The only study on idiopathic scoliosis was conducted by Rowe et al (2006). It was a pilot study to verify the possibility of conducting a larger randomised controlled trial (RCT).…”
Section: Discussionmentioning
confidence: 99%
“…Randomisation costs amounted to 2,176 US dollars (360 dollars per one randomised patient). The authors concluded that appropriate pilot studies are crucial in the process of planning good quality research and their pilot study showed that it is possible and feasible to conduct an RCT assessing the efficacy of chiropractic manipulation in the treatment of idiopathic scoliosis in a large group of patients [21]. tów -współczynnik rekrutacji 17% (6 z 36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation